2007
DOI: 10.1002/ajp.20476
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors in rhesus monkeys (Macaca mulatta) associated with activity counts measured by accelerometer

Abstract: There are large individual differences in the daily pattern and level of physical activity in humans and other species. As it is becoming apparent that activity plays an integral role in a number of physiological processes including arousal, attention, cardiovascular health and body weight regulation, there is an increased interest in quantifying activity. Nonhuman primates are particularly useful experimental models for such studies in that they exhibit a repertoire of activity more similar to humans than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 33 publications
(50 reference statements)
3
39
0
Order By: Relevance
“…Differentiating between active and inactive behaviours is commonly done with variables such as VeDBA or VeDBAs [1,7,18,24]. Interestingly, static acceleration metrics are not always included as discriminators in machine learning algorithms [30] and so our findings suggest that this could be an important factor for other primate researchers to include in their models.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Differentiating between active and inactive behaviours is commonly done with variables such as VeDBA or VeDBAs [1,7,18,24]. Interestingly, static acceleration metrics are not always included as discriminators in machine learning algorithms [30] and so our findings suggest that this could be an important factor for other primate researchers to include in their models.…”
Section: Discussionmentioning
confidence: 87%
“…The list that follows summarises each of these variables, which are numbered 1-25 in round parentheses: (1-3) tri-axial static acceleration [1]; (4-5) pitch and roll [1]; (6) vectorial dynamic body acceleration (VeDBA); (7) smoothed vectorial dynamic body acceleration (VeDBAs) [35,36]; (8-10) tri-axial partial dynamic body acceleration (PDBA) [1]; (11-13) the tri-axial PDBA-to-VeDBA ratio. In addition to these descriptive statistics, we processed the dynamic part of the acceleration further by computing its (14-16) tri-axial power spectrum density (PSD); (17)(18)(19)) maximum frequencies associated with the triaxial PSDs; (20)(21)(22) the second maximum frequencies associated with the tri-axial PSDs; (23-25) the associated frequency for each axis. We provide a full description for each of these variables (1-25), in turn, below.…”
Section: Analyses Of Acceleration Data (Fig 1d)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, there has been a growing interest from primatologists in accelerometers, but the number of studies carried out on free-living animals is still limited Crompton, 1994, 2004;Mann et al, 2005;Sullivan et al, 2006;Papailiou et al, 2008;Ravignani et al, 2013;Wunderlich et al, 2014]. Prior work on primates found that accelerometers can enable investigators to collect valuable information about the behaviour and ecology of a given species.…”
Section: Introductionmentioning
confidence: 99%
“…A novel technique to record the activity of animals involves the use of an accelerometer. Although traditionally used in human medicine, accelerometers have been found to successfully monitor gross motor movement of animals [Mann et al, 2005;Papailiou et al, 2008].…”
Section: Introductionmentioning
confidence: 99%